PROPORTION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN CORONARY HEART DISEASE PATIENTS AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Simanjuntak, Donal Anjar; Pandia, Pandiaman; Tarigan, Amira P (Medicina Biomedica Journal, 2022)
Background: Chronic obstructive pulmonary disease and coronary heart disease are diseases that have several common risk factors, one of which is age and smoking habits. Research conducted by Enriguez et al. reported that CHD patients with COPD had a significantly increased risk of death after 1 year compared to patients with COPD. without COPD, meaning that finding the right diagnosis and appropriate treatment for CHD patients can improve the patient's quality of life and possibly reduce the mortality rate in CHD patients. outpatient treatment at the cardiology outpatient clinic, Haji Adam Malik Hospital, Medan. Results: After examining the history, questionnaire, and post-bronchodilator spirometry, the proportion of COPD patients in CHD patients was 27.50%. Conclusion: This study of the proportion of COPD in patients with coronary heart disease is quite high as much as 27.50%, so it is necessary for clinicians to carry out pulmonary function examinations in CHD patients, especially those who have risk factors for COPD so that clinicians can determine the appropriate management for the patient.